Desarrollo de una proyecto educativo innovador a través de la metodología aprender haciendo: Aplicación a un curso de investigación de mercados (2012)
This work shows the design and application of an unconventional method of a Chilean University, using a learning methodology of "learning-by-doing". This educational project illustrates how it is possible to carry out market researches to enterprises from the class room, where students feel that what they are learning can be applied in the business world, by means of an actual research. This orientation has generated a teaching experiment with high demands of both planning and operational logistics. In addition to that, a research with former students is carried out with the purpose of measuring the impact of the methodology on the formation and development of the students, and the contribution on tools and competences that they visualize from their professional experience.